CUSTOMER RELATIONSHIP MANAGEMENT (CRM) BERBASIS WEB UNTUK MENINGKATKAN DAYA SAING TOKO ONLINE - Kholil, Ishak (LPPM Universitas Nusa Mandiri, 2017)
Customer Relationship Management (CRM) is a thorough business strategy of a company that enables the company to effectively manage relationships with customers. relationships with CRM information technology is very important because, without good information technology capabilities in managing information within the organization, CRM will be paralyzed and has no meaning. A synergy of these two things is needed what today's technology era. To generate a reliable performance of the organization much-needed implementation of both.